Ornithology in laboratory and field - Pettingill, Olin Sewall, 1907-2001 (Academic, 1984)
Ornithology in Laboratory and Field is intended as an aid to ornithological study at the college or university level. Students who lack the background knowledge usually acquired during a course in general zoology or biology should keep it handy for ready reference a standard elementary text on the subject. This book contains extensive material for purely informational reading, possibly enough to supplant the need of an additional textbook. Its principal purpose still complies with the title of its predecessors for it is essentially a manual to guide and assist the student in direct observatio.